An Apoplastic Effector Pat-1Cm of the Gram-Positive Bacterium Clavibacter michiganensis Acts as Both a Pathogenicity Factor and an Immunity Elicitor in Plants - Hwang, In Sun; Oh, Eom-Ji; Song, Eunbee; Park, In Woong; Lee, Yoonyoung; Sohn, Kee Hoon; Choi, Doil; Oh, Chang-Sik (Frontiers in Plant Science, 2022)
Clavibacter michiganensis, a Gram-positive plant-pathogenic bacterium, utilizes apoplastic effectors for disease development in host plants. Here we determine the roles of Pat-1Cm (a putative serine protease) in pathogenicity and plant immunity. Pat-1Cm was found to be a genuine secreted protein, and the secreted mature form did not carry the first 33 amino acids predicted to be a signal peptide (SP). The pat-1Cm mutant impaired to cause wilting, but still caused canker symptom in tomato. Moreover, this mutant failed to trigger the hypersensitive response (HR) in a nonhost Nicotiana tabacum. Among orthologs and paralogs of pat-1Cm, only chp-7Cs from Clavibacter sepedonicus, a potato pathogen, successfully complemented pat-1Cm function in pathogenicity in tomato, whereas all failed to complement pat-1Cm function in HR induction in N. tabacum. Based on the structural prediction, Pat-1Cm carried a catalytic triad for putative serine protease, and alanine substitution of any amino acids in the triad abolished both pathogenicity and HR-inducing activities of Pat-1Cm in C. michiganensis. Ectopic expression of pat-1Cm with an SP from tobacco secreted protein triggered HR in N. tabacum, but not in tomato, whereas a catalytic triad mutant failed to induce HR. Inoculation of the pat-1Cm mutant mixed with the mutant of another apoplastic effector CelA (cellulase) caused severe wilting in tomato, indicating that these two apoplastic effectors can functionally cooperate in pathogenicity. Overall, these results indicate that Pat-1Cm is a distinct secreted protein carrying a functional catalytic triad for serine protease and this enzymatic activity might be critical for both pathogenicity and HR-eliciting activities of Pat-1Cm in plants.